Single umbilical artery and risk of congenital malformation: population‐based study in Norway. (31st March 2020) - Ebbing, C.; Kessler, J.; Moster, D.; Rasmussen, S.
ABSTRACT: Objectives: Single umbilical artery (SUA) is associated with congenital malformations in most organ systems, but reported findings have not been consistent. While it has been suggested that genetic and persisting environmental factors influence the development of SUA, it is not known whether there is an increased risk of recurrence in a subsequent pregnancy of the same woman. The aims of this study were to investigate the occurrence of, and risk factors for, SUA in Norway, to assess its association with congenital malformations and trisomies 13, 18 and 21 and to study the risk of recurrence of SUA in subsequent pregnancies. Methods: This was a population‐based study of all ( n = 918 933) singleton pregnancies of > 16 weeks' gestation recorded in the Medical Birth Registry of Norway from 1999 to 2014. To identify risk factors and congenital malformations associated with SUA, generalized estimating equations and logistic regression were used to calculate odds ratios (OR) with 95% CIs. ORs were also calculated for the recurrence of SUA in subsequent pregnancy. Results: The occurrence of SUA in our population was 0.46% (4241/918 933). Parity ≥ 4, smoking, maternal pregestational diabetes, epilepsy, chronic hypertension, previous Cesarean delivery and conception by assisted reproductive technology increased the odds of having SUA. There was a particularly strong association between SUA and gastrointestinal atresia or stenosis in the neonate, with ORs of 25.8 (95% CI, 17.0–39.1) and 20.3 (95% CI, 13.4–30.9) for esophageal and anorectal atresia or stenosis, respectively, followed by an OR of 5.9 (95% CI, 1.9–18.5) for renal agenesis. SUA was associated with an up to 7–8 times increased risk of congenital heart defects. There was an association with microcephaly, congenital hydrocephalus and other congenital malformations of the brain and spinal cord. Diaphragmatic hernia, limb reductions and cleft lip or palate had a weaker association with SUA, with ORs ranging from 4.8 to 2.8. The associations with trisomy 18 and 13 were equally strong (OR 14.4 (95% CI, 9.3–22.4) and OR 13.6 (95% CI, 6.7–27.8), respectively), and the risk of trisomy 21 was doubled (OR 2.1 (95% CI, 1.2–3.6)). Pregnancies with SUA, with or without an associated malformation, had a 2‐fold increased risk for SUA in a subsequent pregnancy. Conclusions: SUA is associated strongly with gastrointestinal atresia or stenosis, suggesting common developmental mechanisms. The increased risk of recurrence of SUA suggests that genetic and/or persisting environmental factors influence the risk. We found that SUA had equally strong associations with trisomies 13 and 18. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.